Desain buku ajar Ilmu Alamiah Dasar berbasis Worldview Islam - Subagiya, Bahrum; Sauri, Sofyan; Handrianto, Budi; Basri, Samsul; Ulfah, Nur Asiah (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Islamic Worldview has an important role in the development of natural science. Science textbooks in Indonesia are often based on Western science paradigms that contradict the Islamic Worldview. This study aims to design an Islamic Worldview-based Basic Natural Science textbook. The study used a Research and Development (R&D) approach involving needs analysis, designing, and developing textbooks. The results of the study found several important points. First, the emphasis on understanding the creation of the universe by Allah S.W.T. Second, the integration of moral and ethical values in the context of science. Third, the introduction of the contribution of Muslim scientists in the history of science. Fourth, the Islamic Worldview perspective in explaining natural phenomena. Fifth, linking science and Islamic faith. Sixth, emphasizing the search for truth through science channels in the Islamic Worldview. Seventh, correcting science concepts that are not in accordance with the Islamic Worldview. This research contributes to the development of science teaching materials that are more in line with Islamic values, so as to improve students' understanding of natural science and strengthen their Islamic identity. Abstrak Worldview Islam memiliki peran penting dalam pengembangan ilmu pengetahuan alam. Buku-buku pelajaran sains di Indonesia sering didasarkan pada paradigma sains Barat yang bertentangan dengan pandangan dunia Islam. Penelitian ini bertujuan untuk merancang buku ajar Ilmu Alamiah Dasar berbasis Worldview Islam. Penelitian ini menggunakan pendekatan Research and Development (R&D) yang melibatkan analisis kebutuhan, perancangan, dan pengembangan buku ajar. Hasil penelitian menemukan beberapa poin penting. Pertama, penekanan pada pemahaman penciptaan alam semesta oleh Allah S.W.T. Kedua, integrasi nilai-nilai moral dan etika dalam konteks sains. Ketiga, pengenalan kontribusi ilmuwan muslim dalam sejarah sains. Keempat, perspektif Worldview Islam dalam menjelaskan fenomena alam. Kelima, mengaitkan antara sains dan akidah Islam. Keenam, penekanan pada pencarian kebenaran melalui saluran ilmu dalam Worldview Islam. Ketujuh, mengoreksi konsep sains yang tidak sesuai dengan Worldview Islam. Penelitian ini memberikan kontribusi dalam pengembangan bahan ajar sains yang lebih sesuai dengan nilai-nilai Islam, sehingga dapat meningkatkan pemahaman siswa terhadap ilmu pengetahuan alam dan memperkuat identitas keislaman mereka.